Education in Vietnam - London, Jonathan D. (Institute of Southeast Asian Studies, 2011)
Vietnam is a country on the move. Yet contemporary Vietnam's education system is at a crossroads. Rapid economic growth has permitted rapid increases in the scale and scope of formal schooling, but there is a prevailing sense that the current education system is inadequate to the country's needs. Sunny assessments of Vietnam's "achievements" in the sphere of education have given way to a realization that the country lacks skilled workers. Some have even spoken of an "education crisis". These are not abstract concerns. What is occurring in Vietnam's education system today has broad implications for the country's social, political, economic, and cultural development. Featuring contributions from scholars and policy analysts from within and outside Vietnam, Education in Vietnam addresses key issues pertaining to the political economy of education, the provision and payment for primary and secondary education, and the development of vocational and tertiary education. The book marks an important contribution to existing understandings of Vietnam's education system and contributes to broader understandings of social conditions and change in contemporary Vietnam
Title from publisher's bibliographic system (viewed on 24 Nov 2015)
Keywords: Erziehung; Education / Vietnam / Congresses; Bildungssystem; Vietnam; Singapur; Konferenzschrift